A new species of elongate unpatterned moray eel of the genus Gymnothorax (Muraenidae: Muraeninae) from the Bay of Bengal - Mohapatra, Anil; Ray, Dipanjan; Smith, David G.; Mishra, Subhrendu Sekhar (Zootaxa, 2016)
An elongate, brown unpatterned moray eel, Gymnothorax indicus sp. nov., is described based on four specimens collected from the northern Bay of Bengal. The new species is differentiated from other elongate, unpatterned moray eels in having the following combination of characters: anus at about mid-point of body, preanal length 2.0 in total length; snout blunt and short; dorsal fin margin black, 5 mandibular pores; maxillary teeth uniserial, sharp and depressible, total vertebrae 194 (MVF: 9-79-194).